2007
DOI: 10.4103/1319-3767.36745
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the malarial spleen

Abstract: Spontaneous rupture of the spleen is a well-described occurrence in many diseases, being most commonly found in malaria. Exact incidence of this complication is not clear. In this article, we discuss pathology, diagnostic approach and therapeutic options in a patient with malarial splenic rupture. Ruptures of malarial spleens do heal and attempts at splenic lavage/conservative approach should be the aim in their management. Splenectomy should be reserved for those patients with severe rupture or those with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A Medline search for cases of NSR revealed that 454 cases were reported between 1966 and February 2007 [20,21] . Malaria is the most common cause of pathologic rupture of spleen in the tropics, and life-threatening complications occur in up to an estimated 2% of cases [6,7,12,20,22] . Most cases of pathologic rupture of the spleen in malaria occur during acute infection, and usually during the primary attack [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Medline search for cases of NSR revealed that 454 cases were reported between 1966 and February 2007 [20,21] . Malaria is the most common cause of pathologic rupture of spleen in the tropics, and life-threatening complications occur in up to an estimated 2% of cases [6,7,12,20,22] . Most cases of pathologic rupture of the spleen in malaria occur during acute infection, and usually during the primary attack [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Infection, malignancy, metabolic disorders, as well as vascular and hematological diseases, of which only single case reports have been published in the literature, are the usual reasons [3][4][5] . Recently, some authors have reported that spontaneous splenic rupture has been seen as a factor in malaria [6,7] , aortic valve replacement for bacterial endocarditis [8] , normal spleen [9] , factor Ⅷ deficiency, which is a rare autosomal bleeding disorder with a frequency of 1:2 000 000 in the general population [10] , and autologous transplantation for primary systemic amyloidosis [11] . Especially, malaria was discussed retrospectively in all aspects by authors.…”
Section: Introductionmentioning
confidence: 99%
“…Splenomegaly occurs earlier compared to other complications, such as rupture [3,6]. A palpable spleen may be present within 3 to 4 days of the onset of symptoms and may be noted in 50% to 90% of patients with malaria [4,7]. The spleen may subsequently become more hyperemic, swollen and tender with each febrile paroxysm, though partial resolution can occur between paroxysm, though partial resolution can occur between paroxysm.…”
Section: Discussionmentioning
confidence: 99%
“…The management of spontaneous or pathological splenic haemorrhage has been debated constantly. Aggressive management with early surgical intervention is important 9. The survival of patients following splenectomy is probably well correlated with the course of the underlying disease.…”
Section: Discussionmentioning
confidence: 99%